2022
DOI: 10.1590/1678-6971/eramg220152.en
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between emotional intelligence, congruence, and intrinsic job satisfaction

Abstract: Purpose: The purpose of the study was to explore the association between emotional intelligence, person-environment congruence and intrinsic job satisfaction in two professional groups, the first focusing on interpersonal relationships and the second, on data, things, and ideas. Originality/value: The study presents the association between congruence, emotional intelligence and intrinsic satisfaction at work and tests the model in which congruence moderates the association between emotional intelligence and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
1
0
1
Order By: Relevance
“…The results of this study showed a signi cant positive correlation between the total job satisfaction score and the total EI score, as well as the dimensions of EI, including intrapersonal, interpersonal, compatibility, and public mood. In line with our study, the results of other studies have shown a signi cant and positive correlation between EI and job satisfaction [30,31]. Bano and colleagues reported a signi cant and positive correlation between all components of EI, as well as the Total EI score, with job satisfaction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study showed a signi cant positive correlation between the total job satisfaction score and the total EI score, as well as the dimensions of EI, including intrapersonal, interpersonal, compatibility, and public mood. In line with our study, the results of other studies have shown a signi cant and positive correlation between EI and job satisfaction [30,31]. Bano and colleagues reported a signi cant and positive correlation between all components of EI, as well as the Total EI score, with job satisfaction.…”
Section: Discussionsupporting
confidence: 92%
“…However, age and organizational support had an impact on emotional exhaustion [1]. The results of a study showed that emotional skills could predict employees' satisfaction with organizational activities [30]. In another study, the ndings indicated that EI signi cantly in uenced the level of job satisfaction among healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional intelligence and job happiness are very important in the workplace. In the course of organisational life, an individual is given with a competitive framework 7 . The interaction between nurses and patients as well as the rest of the medical staff is strengthened by their emotional intelligence.…”
Section: Introductionmentioning
confidence: 99%
“…Así pues, la IE es un factor individual que desempeña un papel relevante en el afrontamiento positivo de eventos (Batista et al, 2022) que surgen en la vida adulta, como el desempeño académico, laboral, familiar, el desarrollo personal y social, así como la aparición de enfermedades (Gómez-Romero et al, 2018;Villota et al, 2016). Estos sucesos vitales requieren que los adultos desarrollen habilidades emocionales eficaces como respuesta a las demandas de sus roles en la sociedad (Regalado et al, 2022).…”
Section: Introductionunclassified